SEVEN HYPOTHESES FOR AN AESTHETIC OF LIBERATION - Dussel, Enrique (2018)
This article is an advance, for it will be part of a book assembling articles by this author, in which he offers decolonial proposals to diverse topics. In it, we find seven hypothesis that tear out the aesthetic definition developed by the Greek, which is positioned as the ontological starting point of any possible aesthetic. He then talks about the work of art and arrives at the ethic-political dimension of aesthetics, at the aestheticide of the Gre- co-Roman aesthetic, so that this may allow him to talk, then, about a decolonization of aesthetics that will enable the Aesthetic of Liberation, which is his proposal.